Time Efficiency and Cost-Benefit Analysis of New Student Admissions Mobile Application: A Case Study in A Vocational School Palembang - Putri, Indah Pratiwi; Marcelina, Dona; Heryati, Agustina; Permatasari, Indah; Dopri (Yayasan Asmin Intelektual Berkah, 2024)
This study aims to analyze the effectiveness of using an Android mobile application in the new student admission system at a vocational school. The application is designed to replace the manual registration methods, which were previously conducted through Google Forms and WhatsApp communication. By integrating push notifications using Firebase Cloud Messaging (FCM) and a MySQL database, the system enables real-time communication between administrators and prospective students, as well as the automation of admission data management. The Time Efficiency method is used to measure the time saved in the registration and notification process compared to the manual method. Meanwhile, the Cost-Benefit Analysis method is applied to evaluate the ratio between the system implementation costs and the benefits produced, such as reduced operational costs, increased registration speed, and improved administrative staff efficiency.